Protocolo PROCISUR de Verificación y Validación de Soluciones Digitales AgTech (poster) - Calderon Diaz, Facundo Javier; Tallarico, Gabriela Adriana; Mondo, Vitor Henrique Vaz; Best, Stanley; Carrillo, Hugo; Tiscornia, Guadalupe (IICA, 2025)
Poster